2020
DOI: 10.1109/jestpe.2019.2961774
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Internal Energy in MMCs Operating in Grid-Forming Mode

Abstract: With an increasing number of renewable energy resources being integrated into the power system through power electronics, conventional power plants based on large synchronous machines tend to be reduced in the upcoming future. With the Modular Multilevel Converter as the state-of-the-art power electronics solution for power systems, it will be necessary to operate some of these converters in grid-forming mode, in order to either preserve the stability and robustness of the ac grid or as the only solution to ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Assuming that the transformer has no residual flux in the core, the converter can soft-start the ac grid by ramping up the ac voltage in order to eliminate inrush current in the transformer. Assuming a passive R-L grid, grid forming control such as the one detailed in [34], [35] is adopted, with the modification that the converter is not connected on the dc side, therefore the energy balance has to be maintained by circulating currents replenishing the C-stack energy from ES-stacks, as shown in Fig. 14.…”
Section: Active Charging Of the C-stacksmentioning
confidence: 99%
“…Assuming that the transformer has no residual flux in the core, the converter can soft-start the ac grid by ramping up the ac voltage in order to eliminate inrush current in the transformer. Assuming a passive R-L grid, grid forming control such as the one detailed in [34], [35] is adopted, with the modification that the converter is not connected on the dc side, therefore the energy balance has to be maintained by circulating currents replenishing the C-stack energy from ES-stacks, as shown in Fig. 14.…”
Section: Active Charging Of the C-stacksmentioning
confidence: 99%
“…The combination of energy-based internal control and grid-forming based external control of MMC is discussed in [45], [46]. It has been demonstrated that by controlling MMC internal energy, the grid-forming based MMC is identical to an equivalent 2-level VSI.…”
Section: Internal Control Of MMCmentioning
confidence: 99%
“…The voltage at the PCC, denoted by 𝑣 , is also the voltage of the capacitance 𝑐 . This capacitance can be the physical capacitance of an LC filter [49] or the capacitance of an AC component such as an overhead line [50] if there is no filter. The control scheme is composed of the following blocks:…”
Section: B Voltage-source Modementioning
confidence: 99%